The professional methodological teaching performance of the professor of Physical education. Set of parameters for its measurement - Orlando Pedro Suárez Pérez; Pedro Alberto Martínez Hernández; Modesta Moreno Iglesias (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2017)
This work was developed due to the need to attend to the difficulties found in the Physical Education teachers of the municipality of San Juan and Martínez during the development of the teaching-learning process of Basketball, which threaten the quality of the classes, sports results and preparation of the School for life. The objective is to propose parameters that allow measuring the professional teaching methodological performance of these teachers. The customized behavior of the research made possible the diagnosis of the 26 professors taken as a sample, expressing the traits that distinguish their efficiency, determining their potentialities and deficiencies. During the research process, theoretical, empirical and statistical methods were used, which permitted to corroborate the real existence of the problem, as well as the evaluation of its impact, which revealed a positive transformation in pedagogical practice. The results provide a concrete and viable answer for the improvement of the evaluation of the teaching-methodological component of the Physical Education teacher, which constitutes an important material of guidance for methodologists and managers related to the instrumental cognitive, procedural and attitudinal performance , In order to conduct from the precedent knowledge, the new knowledge and lead to a formative process, with a contemporary vision, offering methodological resources to control the quality of Physical Education lessons.